L’espace numérique, un enjeu pour les collectivités locales - Juan-Luis Klein; Ping Huang (Netcom)
Information and communication technologies (ICTs) are part of our society. These interactive socio-technical devices foster the emergence of new territorialities, new social connections and new opportunities for communication, sharing and collaboration. However, the techno-economic determinism that inspires the ICTs industry enhances existing territorial inequalities, giving rise to what is called "digital divide". Inequalities generated by this divide explain the emergence of local community actions to fight against digital exclusion. Through a case study in Montreal, this article illustrates how community-based organizations use ICTs as a means of social integration and contribute to rebuild social cohesion.